A benign gastric ulcer eroding into a splenic artery pseudoaneurysm presenting as a massive upper gastrointestinal bleed - Syed, Shareef M. (J Surg Case Rep, 2014)
Upper gastrointestinal (UGI) bleeding secondary to a ruptured splenic artery (SA) pseudoaneurysm into the stomach is a rare but a life-threatening condition. Owing to the low prevalence, it remains a diagnostic and therapeutic challenge. A frail 77-year-old Caucasian female presented with epigastric pain and hematemesis. Endoscopy was non-diagnostic for an etiology. She then underwent diagnostic angiography that revealed an SA pseudoaneurysm with active contrast extravasation into the stomach. Subsequent transcatheter arterial coil embolization was conducted of the SA. The patient was subsequently taken for a partial gastrectomy, distal pancreatectomy and splenectomy. She had an uncomplicated postoperative course. Diagnosis of an UGI bleeding secondary to a ruptured SA pseudoaneurysm into the stomach remains difficult. However, we report that in a hemodynamically stable patient, a multidisciplinary approach can be taken, with interval optimization of the patient prior to definitive surgery for a satisfactory outcome.